2021
DOI: 10.1021/acsami.1c17706
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategy for a Hydroxide-Triggered pH-Responsive Hydrogel as a Mucoadhesive Barrier to Prevent Metabolism Disorders

Abstract: Excess nutrient uptake is one of the main factors of complications related to metabolism disorders. Therefore, efforts have emerged to modulate nutrient transport in the intestine. However, current approaches are mainly invasive interventions with various side effects. Here, a pH-responsive hydrogel is formulated by acidifying the hydroxide compounds within sucralfate to allow electrostatic interactions between pectin and aluminum ions. The pH responsiveness relies on the alternation of cations and hydroxide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
(60 reference statements)
1
13
0
Order By: Relevance
“…To mimic the intestinal environment, the syringe pumping rate is in accordance with the shear force produced during intestinal peristalsis as 1.8 μ N cm −1 . 16 The result in vitro showed that the mucoadhesive property of AC is better than alginate under such conditions with intestinal epithelioid cell line, IEC-6 [ Figs. 4(d) and 4(e) ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To mimic the intestinal environment, the syringe pumping rate is in accordance with the shear force produced during intestinal peristalsis as 1.8 μ N cm −1 . 16 The result in vitro showed that the mucoadhesive property of AC is better than alginate under such conditions with intestinal epithelioid cell line, IEC-6 [ Figs. 4(d) and 4(e) ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the material which formed intestinal coating has been proved to decrease the nutrition uptake. 16 Therefore, we aim to engineer the chemical properties of alginate for a longer retention time by investigating the microenvironment where the material attaches the mucus layer. The mucus layer mostly consists of mucin, a kind of glycoprotein with a free thiol group for oxidation–reduction reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides participate in many biological activities, such as cytoskeleton formation, energy metabolism, blood glucose regulation and immunity modulation, are biocompatible and biodegradable, and can be easily extracted, processed and modified. Polysaccharides extracted from plants (for example, alginate 105,106 , cellulose 107 , starch 108 , carrageenan 109 , pectin 110 , guar gum 109 , mannan 111 , glucomannan 112 and inulin 113 ), animals (for example, chitosan 101,114 , hyaluronate 5 and chondroitin sulfate 115 ) and microbes (for example, pullulan 116 and β-glucan 117 ) are being explored for oral drug delivery. Polysaccharide nanoparticle formulations can orally deliver small molecules, oligonucleotides, peptides and proteins 94 .…”
Section: Biological Materialsmentioning
confidence: 99%
“…Compared with traditional hydrogels, intelligent hydrogels can achieve multiple, variable, controllable and reversible changes in their shape and properties in a manner of space or time, thus greatly adapting to the complex application environment in vitro and in vivo. [37][38][39][40][41] Recently, various intelligent hydrogels, such as light-responsive hydrogels, [42][43][44][45][46] thermal-responsive hydrogels, [47][48][49][50][51] pH-responsive hydrogels, [52][53][54][55][56] ultrasound-responsive hydrogels, [57][58][59] ion-responsive hydrogels, [60][61][62] etc., have been developed and showed amazing biomedical applications. Among them, as a new class of intelligent hydrogels, ultrasound-responsive hydrogels have already exhibited irreplaceable application prospects.…”
Section: Introductionmentioning
confidence: 99%